Linking self-leadership to proactive work behavior: A network analysis - Itsara Boonyarit (Cogent Business & Management, 2023)
Proactive work behavior (PWB) is a complex phenomenon that individuals exhibit self-initiative and taking anticipatory action in multiple forms including taking charge, voice, individual innovation, and problem prevention. The current study used a network analysis approach to investigate the associations between self-leadership and the forms of PWB through the lens of the Performance Mechanism Model. Data were collected from 256 operational employees from a state-owned enterprise in Thailand, and a partial correlation network was estimated by using EBIC Graphical LASSO. Findings showed positive associations between self-leadership and two forms of PWB, i.e. taking charge and individual innovation, and also were positively related to psychological empowerment and role-breadth self-efficacy (RBSE). Centrality indices indicated that voice and individual innovation were the most central behaviors in the network. Furthermore, RBSE has emerged as a significant pathway in the link between self-leadership and PWB. Practical implications and future research are discussed.
Keywords: 650; network analysis; psychological empowerment; proactive work behavior; role-breadth self-efficacy; Self-leadership